2008
DOI: 10.1007/s00345-008-0282-z
|View full text |Cite
|
Sign up to set email alerts
|

Extra-anatomical transobturator bypass graft for femoral artery involvement by metastatic carcinoma of the penis: report of five patients

Abstract: The use of the transobturator bypass can benefit patients presenting with penile SCC and inguinal lymph nodes metastasis involving the femoral vessels, allowing resection of extensive tumor lesions, as well as avoidance of local complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Metastatic SCC of the inguinal lymph node has been frequently reported in penile cancer. 3,4) In our patient, therefore, lymph node metastasis of penile cancer was most suspected, however, a definite abnormality was not identifiable even by FDG-PET/CT in the penis.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Metastatic SCC of the inguinal lymph node has been frequently reported in penile cancer. 3,4) In our patient, therefore, lymph node metastasis of penile cancer was most suspected, however, a definite abnormality was not identifiable even by FDG-PET/CT in the penis.…”
Section: Discussionmentioning
confidence: 59%
“…2) However, a metastatic inguinal lymph node carcinoma frequently involves the femoral vessels in its advanced stage and leads to massive bleeding and even death. 3,4) with a blood pressure of 72/38 mmHg and an irregular heart rate of 116/min. The eroded ulceration of the left groin was 5 × 5 cm in size and emitted a foul odor resulting from infection and necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ulceration of nodes and fixity occurs in the later stages of malignancy. Blowout of the underlying femoral vessels is one of the terminal events in such cases [3,4]. There are some peculiarities in this patient.…”
Section: Discussionmentioning
confidence: 73%
“…However, we agree that obturator bypass represents one of the best time honored treatment options when complex infections occur in the groin [ 5 ]. The literature reports have suggested that obturator bypass is safe, effective and durable method with primary patency rates of 76% at 24 months in clinical series [ 3 , 8 10 ]. In addition, the literature regarding mortality rates ranges from 0% to 17% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%